From innovation capability to green innovation capability: Evidence from Chinese big tech firms - Martín Hernani-Merino; Jorge Tello-Gamarra; David Mayorga; Julio Zevallos (Journal of Economy and Technology)
Innovation capability as a source of competitive advantage for firms is a consolidated topic in the literature. However, there is still little evidence about the green characteristics that innovation capability incorporates. This article aims to identify the innovation capability and analyze the existence of green variables in said capability. We conducted a multiple case study comprising four Big Tech firms from the Chinese technology industry. The results show that each of the capabilities involved in the innovation capability (technological, operational, managerial, marketing, and learning) demonstrates a green variable. As a second result, we define the concept of green innovation capability as a repertoire of abilities, skills, knowledge, and routines for the firm to design, produce, and transact green products and services. Furthermore, we propose the concepts of the capabilities that form the green innovation capability.